2020
DOI: 10.1002/app.50087
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the preparation of maleic anhydride grafted poly (lactic acid) by reactive processing for poly (lactic acid)/carbon nanotubes nanocomposites

Abstract: An effective strategy to increase the properties of poly (lactic acid) (PLA) is the addition of carbon nanotubes (CNT). In this work, aiming to improve the surface adhesion of PLA and CNT a new compatibilizer agent was prepared by reactive processing, PLA grafted maleic anhydride (PLA‐g‐MA) using benzoyl peroxide and maleic anhydride. The effectiveness of the PLA‐g‐MA as a compatibilizer agent was verified for PLA/PLA‐g‐MA/CNT nanocomposites. PLA and PLA‐g‐MA samples were characterized by Fourier transform inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…It is expected that if degradation has been found during the reactive extrusion, the samples will show a clear reduction in the Mn and Mw and an increase in the PDI. Other authors have confirmed this by DSC or tensile strength tests [ 25 ], however Mw analysis is more accurate. Results are shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 62%
“…It is expected that if degradation has been found during the reactive extrusion, the samples will show a clear reduction in the Mn and Mw and an increase in the PDI. Other authors have confirmed this by DSC or tensile strength tests [ 25 ], however Mw analysis is more accurate. Results are shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 62%
“…The most widely used reagent for functionalizing the PLA chain is maleic anhydride (MA) due to its good chemical reactivity, low toxicity and good stability to the experimental synthesis conditions [21][22][23]. The grafting of MA onto the PLA backbone results in a reactive compatibilizer due to the presence of the anhydride function.…”
Section: Direct Functionalization Of Pla Backbone: Towards Pla-based ...mentioning
confidence: 99%
“…Compatibilizing effects of PLA-g-MA on the properties of PLA/Soy Protein concentrate (SPC) blends were demonstrated by a 19% increase in tensile strength compared to Compatibilizing effects of PLA-g-MA on the properties of PLA/Soy Protein concentrate (SPC) blends were demonstrated by a 19% increase in tensile strength compared to the non-compatibilized blend [62]. Finally, PLA-g-MA also has the ability to provide some compatibility to PLA/mineral mixtures such as PLA/carbon nanotubes [22], PLA/Titanium oxide [63], PLA/halloysite [64], PLA/hydroxyapatite [65], PLA/talc [66], PLA polyhedral oligomeric silsesquioxane (POSS) [67].…”
Section: Pla-g-polyestermentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous works that reported on recovery by recycling, biodegradation test, or even toxicity (such as ecotoxicity with plants) of biodegradable polymers are observed [1,4,[10][11][12], the composites or nanocomposites produced with these polymers have been very little considered [13,14]. Commonly, biodegradable polymers are processed with other polymers (polymer blends) or reinforced with filler or nanofiller, generating composites or nanocomposites with enhanced properties [2,[15][16][17][18][19][20][21][22][23][24][25]. Few studies address the effect of the addition of the nanofiller on the polymer biodegradation property [4,21,[26][27][28][29][30][31][32], and even fewer studies have investigated what happens to the nanofillers after polymer biodegradation [26].…”
mentioning
confidence: 99%